A BIBLIOMETRIC ANALYSIS OF DENTAL LITERATURE PUBLISHED IN JOURNAL OF COLLEGE OF PHYSICIANS AND SURGEONS OF PAKISTAN, JCPSP - Adnan, Samira; Zafar, Kamil; Farhan Raza Khan (Journal of Ayub Medical College Abbottabad, 2022)
Background: Bibliometric analysis of a particular specialty published in single journal allows the identification of publication trends, areas of focus and potential domains for future research that could be publishable within the scope of that journal. This study aimed to analyse the characteristics of dental literature published in JCPSP in order to determine the trend of publication of dentistry-related papers in this journal. Methods: An electronic and hand search was conducted of all JCPSP issues from 1991 till June 2018. The selected articles were analysed for year of publication, field of study, type of article, the names of first author, their gender and affiliation (institute, country), number of authors in each publication and citation count. Data was statistically analysed using SPSS version 20.0. Results: Out of approximately 5,400 published articles, 253 were included for analysis. Articles related to Oral and Maxillofacial surgery were in majority (n=54), followed by Operative Dentistry and Endodontics (n=38). Most (n=103) were original research articles. Pakistani authors contributed the majority of articles (n=184). The greatest number of dental articles were published in the year 2014 and 2017 (n=30). The institutions with the highest number of dental papers were Aga Khan University, Karachi and NIMS Dental College, Jaipur, India. The majority of articles were by Manas Bajpai as first author (n=22 articles). The highest citation count was found to be 55. Conclusion: Overall, the proportion of dentistry related articles published in JCPSP is low (4.6%). Researchers working in dental specialties where few publications were observed could be invited to submit relevant publications to JCPSP to broaden the scope of the journal. Foreign authorship should be encouraged to further elevate the standing of this journal. A separate journal for dental research in light of the continually increasing number of dental specialists and researchers is the need of the hour